Penerimaan Generasi Muda Betawi Terhadap Sosok Benyamin dalam Film Benyamin Biang Kerok 2018 - Suharman, Tri (Jurnal Dakwah Tabligh, 2024)
The Movie Benyamin Biang Kerok, released in 2018, told the story of Pengki, the son of rich Betawinese who often spends his parents' money. He helps the poor like Robin Hood by stealing money from evil businessmen. The movie, starring Reza Rahadian, Rano Karno, Meriam Bellina, is based on the film with the same title that actor Benyamin Sueb plays. This research uses the reception method and aims to find out the acceptance of young Betawinese towards the figure of Benyamin in the movie, played by Reza Rahadian, who is not a Betawi actor like Benyamin Sueb. This research uses the reception analysis method that views media as integrated into a person’s social life so that media content can be interpreted differently by different recipients. In this study, the researcher had eight Betawinese informants and analyzed data from the interview by using Stuart Hall's decoding-encoding concept. The result of this research proves that the majority of Betawi informants have a different reception to the message, text, or code conveyed in the film.